Mitochondrial ROS triggers mitophagy through activating the DNA damage response signaling pathway - Qi-Qiang Guo; Shan-Shan Wang; Xiao-You Jiang; Xiao-Chen Xie; Yu Zou; Jing-Wei Liu; Yang Guo; Yu-Han Li; Xi-Yan Liu; Shuang Hao; Xin-Yue Zhang; Xiao-Xu Wu; et al. (Proceedings of the National Academy of Sciences, 2025)
The homeostatic link between the production of mitochondrial ROS (mtROS) and mitophagy plays a significant role in how cells respond to various physiological and pathological conditions. However, it remains unclear how cells translate oxidative stress signals into adaptive mitophagy responses. Here, we show that mtROS act as signaling molecules that activate the ataxia-telangiectasia mutated (ATM)-cell cycle checkpoint kinase 2 (CHK2), a DNA damage response (DDR) pathway. When activated, CHK2 regulates three critical steps in mitophagy. First, CHK2 phosphorylates mitochondrial membrane protein ATAD3A at Ser371, which inhibits the transport of PINK1 to the inner mitochondrial membrane and leads to the accumulation of PINK1 and the commencement of mitophagy. Second, activated CHK2 targets the autophagy adaptor OPTN at Ser177 and Ser473, thereby enhancing the targeting of ubiquitinated mitochondria to autophagosomes. Finally, CHK2 phosphorylates Beclin 1 at Ser90 and Ser93, hence promoting the formation of autophagosomal membranes. Consistent with these effects, Chk2 −/− mice show impaired mitophagic induction and impaired recovery in a ROS-dependent model of renal ischemia–reperfusion. Our study reveals a mtROS-triggered adaptive pathway that coordinates mitophagic induction, in order to protect cells and tissues exposed to pathophysiological stress-induced damage.